Managing Business Intelligence Transition: Support and User Acceptance in Data Analytics Adoption - Saari, Henri (2024)
The emergence of big data analytics has been apparent for a while now. Data quantities get bigger, and machines get smarter by the day, enabling new methods of analysis and insight. Organizations are required to harness these data capabilities to stay competitive in a rapidly evolving environment, which has led to organizations treating data as an organizational asset. This has led to the rise of cloud-based massive data storing capabilities and modern business intelligence (BI) tools, that deliver insights to business users in real time. However, replacing the old reporting systems with modern BI solutions can be a lengthy and complex process, requiring understanding of technical, business, and organisational aspects. Organizational change is typically slow, difficult, and expensive of nature, requiring careful planning, communication, and time to succeed. When it comes to the process of renewing or implementing analyt-ics and BI, assuring the onboarding of end-users is exceptionally important, as the value gained from BI systems is dependent on insights and decision making made by the users. If the end-users do not accept the system or are not sup-ported throughout the implementation, shortcomings are bound to occur.